Diversity, composition, structure and canopy cover of mangrove trees in six locations along Bintuni riverbank, Bintuni Bay, West Papua, Indonesia - MARKUS SRAUN; RONI BAWOLE; JONNI MARWA; ANTON SILAS SINERY; REINARDUS LIBORIUS CABUY (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Srau M, Bawole R, Marwa J, Sinery AS, Cabuy RL. 2022. Diversity, composition, structure and canopy cover of mangrove trees in six locations along Bintuni riverbank, Bintuni Bay, West Papua, Indonesia. Biodiversitas 23: 5835-5843. Mangroves provide various benefits of ecological and socio-economic aspects. Such benefits could be delivered if mangrove vegetation is in good condition, indicated by several ecological parameters. This study was conducted to investigate the diversity, composition, structure, and canopy cover of mangrove trees along Bintuni riverbank, Bintuni Bay, West Papua, Indonesia. There were six different locations representing biotic and abiotic conditions. The study only focused on the mangrove tree stage with a total of 175 plots established, of which each plot had a size of 10 × 10 m. The name of mangrove species, tree diameter, total height, and canopy cover percentage was recorded and measured. The result showed that the diversity and composition of mangrove trees varied among the six locations indicated by the importance value index (IVI) parameter. The estuary and sub-estuary areas were dominated by Rhizophora mucronata, while in the further area from the estuary toward the land, the dominant mangrove species was Avicennia sp. The highest number of mangrove trees was found in Kampung Lama 1 with 989 trees/ha (593 trees in 60 plots) with an average diameter of 18.8077 cm (SD±7.0279) and an average height of 8.9477 m (SD±2.2814). The lowest tree distribution was found in Kampung Masuhi with 940 trees/ha (94 trees in 10 plots) with an average diameter of 15.4787 m (SD±3.8205). The highest average of canopy covers was noted in the sub-river estuary with a percentage of 86.97% (SD±85) and the lowest percentage was in Kampung Masina with 59.89% (SD±124.85). Statistical analysis of variance (ANOVA) showed that there was a significant difference in terms of average tree diameter and height among the six locations with a p-value of 0.00021 < 0.05 at 95% CI. There was a strong positive correlation between tree diameter and height, as indicated by R2 of 0.69. In addition, a statistical test of analysis of variance from each location was significantly different among these six locations.